Single-cell immunopathology of recurrent acute generalized exanthematous pustulosis associated with vancomycin - Eric M. Mukherjee, MD, PhD; Andrew Gibson, PhD; Matthew S. Krantz, MD; Rama Gangula, MS; Amy M. Palubinsky, PhD; Alan S. Boyd, MD; Jeffrey P. Zwerner, MD, PhD; Anna K. Dewan, MD, MS; Nontaya Nakkam, PhD; Katherine C. Konvinse, MD, PhD; Yueran Li, PhD; Ramesh Ram, PhD; et al. (Journal of Allergy and Clinical Immunology: Global)
Background: Acute generalized exanthematous pustulosis (AGEP) is a severe cutaneous adverse reaction to medication that presents within 72 hours of exposure with erythematous papules and plaques with overlying pustules. The immunopathogenesis and predisposing factors of AGEP are not well characterized. Objective: To better understand the genetic risk factors and single-cell immunopathogenesis of AGEP, we longitudinally characterized a patient with recurrent AGEP after an initial episode triggered by vancomycin. Methods: A clinical timeline over an 8-year period was paired with skin testing, histopathology, and immunogenetic and other testing at 3 time points. Skin biopsies performed on affected skin (positive vancomycin-delayed intradermal testing [IDT]) and unaffected control skin 8 years after the initial event were subjected to single-cell sequencing to measure gene and protein expression. Results: The patient was HLA-A∗32:01 positive, which has been associated with vancomycin-induced drug reaction with eosinophilia and systemic symptoms. IDT remained positive over time, despite recurrent reactions without drug exposure. Clinical features and histopathology of IDT-positive skin were consistent with AGEP. Single-cell analysis of affected skin showed polyclonal TH17-like cells with gene expression signatures similar to T-cell response during prevalent infectious diseases. Conclusions: This patient exhibited persistent vancomycin-positive IDT despite distinct nondrug episodes of ALEP/AGEP. This suggests that AGEP may be triggered by both antigen-specific and non–antigen-specific factors. AGEP-affected skin showed an inflammatory infiltrate with a TH17-like effector population, which may represent potentially actionable targets for therapeutic intervention. The presence of HLA-A∗32:01, a defined risk factor for vancomycin-induced drug reaction with eosinophilia and systemic symptoms, may indicate a shared predisposition, warranting further study.